Evaluation of microbubbles as contrast agents for ultrasonography and magnetic resonance imaging. - Ling Li; Qiang Wei; Hong-Bo Li; Song Wen; Gao-Jun Teng (PLoS ONE, 2012)
BACKGROUND: Microbubbles (MBs) can serve as an ultrasound contrast agent, and has the potential for magnetic resonance imaging (MRI). Due to the relatively low effect of MBs on MRI, it is necessary to develop new MBs that are more suitable for MRI. In this study, we evaluate the properties of SonoVue® and custom-made Fe(3)O(4)-nanoparticle-embedded microbubbles (Fe(3)O(4)-MBs) in terms of contrast agents for ultrsonography (US) and MRI. METHODOLOGY/PRINCIPAL FINDINGS: A total of 20 HepG2 subcutaneous-tumor-bearing nude mice were randomly assigned to 2 groups (i.e., n = 10 mice each group), one for US test and the other for MRI test. Within each group, two tests were performed for each mouse. The contrast agent for the first test is SonoVue®, and the second is Fe(3)O(4)-MBs. US was performed using a Technos(MPX) US system (Esaote, Italy) with a contrast-tuned imaging (CnTI™) mode. MRI was performed using a 7.0T Micro-MRI (PharmaScan, Bruker Biospin GmbH, Germany) with an EPI-T(2)* sequence. The data of signal-to-noise ratio (SNR) from the region-of-interest of each US and MR image was calculated by ImageJ (National Institute of Health, USA). In group 1, enhancement of SonoVue® was significantly higher than Fe(3)O(4)-MBs on US (P<0.001). In group 2, negative enhancement of Fe(3)O(4)-MBs was significantly higher than SonoVue® on MRI (P<0.001). The time to peak showed no significant differences between US and MRI, both of which used the same MBs (P>0.05). The SNR analysis of the enhancement process reveals a strong negative correlation in both cases (i.e., SonoVue® r = -0.733, Fe(3)O(4)-MBs r = -0.903, with P<0.05). CONCLUSIONS: It might be important to change the Fe(3)O(4)-MBs' shell structure and/or the imagining strategy of US to improve the imaging quality of Fe(3)O(4)-MBs on US. As an intriguing prospect that can be detected by US and MRI, MBs are worthy of further study.